2010
DOI: 10.1186/1471-2334-10-103
|View full text |Cite
|
Sign up to set email alerts
|

Cellular immunity in children with successful immunoprophylactic treatment for mother-to-child transmission of hepatitis B virus

Abstract: BackgroundThe administration of hepatitis B immunoglobulin followed by hepatitis B vaccine can result in a protective efficacy of almost 90% in mother-to-child transmission of hepatitis B virus (HBV). However, little is known about immunity against HBV infection in children after immunoprophylactic treatment. We tried to assess the association between T-cell responses and viremia in children after successful prophylactic treatment.MethodsThirteen children and their 8 HBV carrier mothers (8 families), who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
0
15
0
2
Order By: Relevance
“…24 Such T-cell responses, although not related to detectable viremia, are due to viral exposure. Detection of such responses at birth supports the hypothesis of in utero exposure.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…24 Such T-cell responses, although not related to detectable viremia, are due to viral exposure. Detection of such responses at birth supports the hypothesis of in utero exposure.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, HBV viremia following successful immunoprophylaxis has been reported even among older children, born to either HBeAg(+) or HBeAg(−) mothers in endemic areas, which may have significant implications and needs to be confirmed. 15,16,20,24 High maternal viremia and HBeAg(+) status are identifiable risk factors for HBV viremia and infection despite immunoprophylaxis and therefore have been associated with the occurrence of in utero HBV transmission. [11][12][13][14][25][26][27][28][29] In our study, children of HBeAg(−) mothers had a similar incidence of neonatal viremia probably due to the small number of HBeAg(+) mothers studied.…”
Section: Discussionmentioning
confidence: 99%
“…20 Furthermore, a better analysis of data generated in natural HBV infection reveals that a proportion of neonates exposed to HBV at birth, mount a HBV-specific T-cell response. For example, two independent studies performed in HBsAg-negative children born to HBV-positive mothers 21,22 have demonstrated the presence of core and polymerase-specific T cells. Neonates of HBV 1 mothers have also been shown to have minimal or normal dendritic cell functions.…”
mentioning
confidence: 99%
“…2,16,18,19 HBV-specific T-cell responses, especially CTLs, play a role in the control of HBV infection in children born to HBsAg-positive mothers after immunoprophylactic treatment. 20 The aim of the present study was to evaluate the immune effects of a new microsphere vaccine, which could provide an effective means to combat chronic hepatitis B infection. Since the adsorbed antigen is much easier to release from the surface of the microsphere rather than from encapsulated microspheres used in controlled-release formulations, the microsphere vaccine formulated in this study could evoke a much quicker immune response.…”
Section: Discussionmentioning
confidence: 99%